The front page : everyday Ignatian spirituality - Gleeson, Christopher, 1943- (ATF Press, 2011)
Christopher Gleeson SJ, was born in Melbourne and educated by the Presentation Sisters and the Society of Jesus (Jesuits) whose ranks he joined in 1962. Ordained priest in 1975, he has spent most of his working life as a teacher and administrator in Jesuit schools, nearly twenty-one of which as Head of both Xavier College in Melbourne and St Ignatius' College, Riverview, in Sydney. His peers elected him to serve as Chair of the Association of Heads of Independent Schools of Australia from 1999 to 2001. Since leaving Riverview at the end of 2002, he has been Director of Jesuit Publications (now.